A niobium-silicon-based high-temperature alloy added with cobalt aluminate coupled with ultrasonic treatment and a preparation method thereof

CN118222899BActive Publication Date: 2026-11-03HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410365889.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-28
Publication Date
2026-11-03
Estimated Expiration
2044-03-28

AI Technical Summary

Technical Problem

Niobium-silicon-based superalloys have poor room temperature fracture toughness, making it difficult to meet the application requirements of high-temperature components in aerospace engines.

Method used

Adding cobalt aluminate as a refining agent to niobium-silicon-based superalloys, combined with ultrasonic treatment, allows the cavitation and acoustic flow effects generated by ultrasound to influence the formation and distribution of the phases, refining the microstructure and generating fine silicide structures.

Benefits of technology

It significantly improves the room temperature fracture toughness of niobium-silicon-based superalloys, reduces stress concentration at the tips of silicide phases, and enhances the mechanical properties of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118222899B_ABST
    Figure CN118222899B_ABST
Patent Text Reader

Abstract

The application discloses a niobium-silicon based high-temperature alloy added with cobalt aluminate coupled with ultrasonic treatment and a preparation method thereof, and relates to the technical field of high-temperature alloy preparation. The application solves the problem of poor room temperature fracture toughness of the existing niobium-silicon based high-temperature alloy. In the application, the niobium-silicon alloy is prepared according to the atomic percentage of raw materials, and a refiner CoAl2O4 is added, and the mass of the refiner is 0.2% of the mass of the ingot; the niobium-silicon based high-temperature alloy is prepared in a vacuum non-consumable arc furnace; the button ingot is repeatedly melted for 4-5 times, the current is reduced to 0 A after the melting is completed, and the sample is taken out; the refiner CoAl2O4 and the button ingot are placed in a crucible, the button ingot is again melted by assisting ultrasonic treatment, and the current is reduced to 0 A after the melting is completed. By adding the refiner CoAl2O4 and coupling 0-320s ultrasonic treatment, the heterogeneous nucleation particles increase, more cracks are absorbed in the fracture process, and the room temperature fracture toughness is increased. The application is used for preparing the niobium-silicon based high-temperature alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy preparation technology, specifically to a niobium-silicon-based superalloy with added cobalt aluminate coupled with ultrasonic treatment and its preparation method. Background Technology

[0002] With the continuous development of aerospace technology, the requirements for the high-temperature resistance of materials for high-temperature components of aircraft engines are gradually increasing. Nickel-based superalloys, widely used since the 1950s, have reached 85% of their melting point in service, making it difficult to meet the temperature requirements of new aero-engine turbine blades. Therefore, the need for a new generation of high-temperature structural materials is urgent. Niobium-silicon based alloys, due to their lower density (7.3-8.6 g / cm³), offer a solution. 3 Niobium-silicon-based alloys are considered a highly promising high-temperature composite structural material due to their high melting point (>1800 ℃), offering significant advantages in weight reduction and high-temperature strength. However, their poor room-temperature fracture toughness and difficult machining make them unsuitable for the forming processes required for niobium-silicon-based alloy parts, severely limiting their application in high-temperature components of aircraft engines. Therefore, improving the room-temperature fracture toughness of niobium-silicon-based superalloys is of great significance for their engineering applications, and it is also a pressing problem to be solved in the process of niobium-silicon-based superalloys becoming a new generation of high-temperature resistant components for aerospace applications.

[0003] Niobium-silicon-based superalloys are mainly composed of room-temperature toughened Nbss phases and high-temperature reinforced silicide phases (including Nb3Si, α-Nb5Si3, β-Nb5Si3, and γ-Nb5Si3 phases). Among these, the silicide phases exhibit intrinsic brittleness compared to the Nbss phase, which is detrimental to the room-temperature fracture toughness of niobium-silicon-based superalloys. Therefore, existing niobium-silicon-based superalloys suffer from poor room-temperature fracture toughness. Summary of the Invention

[0004] The purpose of this invention is to solve the problem of poor room temperature fracture toughness in existing niobium-silicon-based superalloys, and to provide a niobium-silicon-based superalloy with added cobalt aluminate coupled with ultrasonic treatment and its preparation method.

[0005] The technical solution of this invention is: A niobium-silicon-based superalloy with added cobalt aluminate coupled with ultrasonic treatment is disclosed. The atomic ratios of the raw materials of the niobium-silicon-based superalloy are as follows: Nb 57.95%, Si 16%, Ti 20%, Zr 3%, C 3%, and Sc 0.05%. During the smelting process, an excess of CoAl2O4 refining agent is added, with a mass of 0.2% of the required ingot mass. The niobium-silicon-based superalloy is obtained by coupled ultrasonic treatment for 0~320 s.

[0006] This invention also provides a method for preparing a niobium-silicon-based superalloy with added cobalt aluminate coupled ultrasonic treatment, which includes the following steps: Step 1: Raw material preparation: Based on the required ingot mass, weigh the raw materials according to the atomic ratio: Nb 57.95%, Si 16%, Ti 20%, Zr 3%, C 3%, Sc 0.05%; add CoAl2O4 in excess, with a mass of 0.2% of the required ingot mass. Step 2: Preparations for smelting: The raw materials were placed in a water-cooled copper crucible of a vacuum non-consumable arc furnace; pure Ti blocks were placed in another crucible of the vacuum non-consumable arc furnace. Step 3, Smelting: Close the furnace door and evacuate to a vacuum level of 1×10⁻⁶. -3 Below Pa, high-purity argon gas is then introduced into the furnace to 0.5 MPa. The vacuuming and argon filling process is repeated 1-2 times. During the melting process, pure Ti blocks are melted first to absorb residual oxygen, and then the raw materials are melted. After the melting is completed, button ingot samples are obtained. The button ingot samples are repeatedly melted 4-5 times, and the samples are taken out after cooling. Step 4: Refine the coupled ultrasound processing: The weighed CoAl2O4 blue powder was evenly placed on the crucible base, and then the cooled button ingot sample was placed on it. The vacuuming and argon filling steps in step three were repeated to melt the button ingot again. At the same time as the melting current was reduced, the ultrasonic treatment equipment was turned on. The ultrasonic treatment time was 0~320 s. After cooling, the niobium silicon-based high-temperature alloy button ingot with added cobalt aluminate coupled ultrasonic treatment was obtained.

[0007] Furthermore, in step one, Nb is φ 2×2 mm particles, Si is irregular flakes, Ti is high-purity sponge titanium, Zr is 1~2 mm irregular particles, C is carbon powder with a particle size of 5 μm, Sc is filamentous material with a length of φ 0.5 mm and different lengths, and CoAl2O4 is blue powder with a particle size of 150 nm.

[0008] Furthermore, the purity of the metal raw materials in step one is all above 99.95%.

[0009] Furthermore, in step one, C and Sc are wrapped with aluminum foil.

[0010] Furthermore, in step two, the placement order is as follows: Step 21: Place the aluminum foil containing the C powder and Sc wire at the bottom of the crucible to prevent the electric arc from blowing the C powder and Sc wire away during melting; Step 22: Place the Si wafer and Zr particles; Steps 2 and 3: Place the Ti block and Nb block on top.

[0011] Furthermore, during the melting process in step three, the melting current is increased by 300 A every 5 seconds to reach 600 A, and maintained in the molten state for 10 to 15 seconds. After melting, the current is gradually reduced by 50 A every 10 seconds until it reaches 0 A, at which point the power is turned off.

[0012] Furthermore, in step four, the rate of increase of the melting current is consistent with that in step three. After maintaining the melt in the molten state for 20 to 30 seconds, the ultrasonic treatment device is turned on to treat the melt for 0 to 320 seconds, while the melting current is reduced to 0 A. The rate of decrease of the melting current is consistent with that in step three.

[0013] Furthermore, in step four, the ultrasonic processing equipment is non-contact, with the top of the ultrasonic probe in close contact with the bottom of the cold crucible, and the bottom of the ultrasonic probe connected to the ultrasonic controller via an ultrasonic generator rod.

[0014] Compared with the prior art, the present invention has the following advantages: 1. This invention utilizes the cavitation and acoustic flow effects generated by ultrasound to influence phase formation and distribution, refine the microstructure, and thereby eliminate coarse dendrites, forming a fine microstructure to improve performance. Cobalt aluminate, as a stable grain refiner, can be widely used in iron-based, cobalt-based, and nickel-based high-temperature alloys. In high-temperature melts, cobalt aluminate can react with active elements in the alloy melt to reduce metallic cobalt. Metallic cobalt provides heterogeneous nucleation sites for the formation of the matrix phase in high-temperature alloys, thus refining the grain size.

[0015] 2. Under the action of ultrasonic treatment coupled with cobalt aluminate, the niobium-silicon-based superalloy of the present invention gradually transforms the elongated silicide phase into a near-spherical shape and gradually reduces its size, thereby reducing stress concentration at the crack tip during crack propagation and improving the room temperature fracture toughness of the niobium-silicon-based alloy.

[0016] 3. The cobalt aluminate refiner added to the niobium-silicon-based superalloy of the present invention reacts with the high-temperature melt during solidification to generate metallic cobalt. The metallic cobalt, as a heterogeneous nucleation point, provides a nucleation substrate for the solidification of the niobium-silicon-based high-temperature melt. At the same time, under the action of coupled ultrasonic treatment, the size of silicides in the niobium-silicon-based alloy is significantly reduced, effectively refining the microstructure. More cracks are generated during the fracture process, absorbing more energy and significantly improving the room temperature fracture toughness of the niobium-silicon-based superalloy.

[0017] 4. The niobium-silicon-based high-temperature alloy prepared by the method of the present invention is produced in a vacuum non-consumable arc furnace. The cost of cobalt aluminate is low, and the process is relatively simple, which has strong application value. Attached Figure Description

[0018] Figure 1 The X-ray diffraction patterns are those of the niobium-silicon-based high-temperature alloys prepared in Examples 1 to 4 of this invention.

[0019] Figure 2 The images show the microstructure of the niobium-silicon-based high-temperature alloys prepared in Examples 1 to 4 of this invention.

[0020] Figure 3 The room temperature fracture toughness K of the niobium-silicon-based superalloys prepared in Examples 1 to 4 of this invention. Q Value results graph. Detailed Implementation

[0021] Specific Implementation Method 1: The atomic ratio of the raw materials for the niobium-silicon-based superalloy in this implementation method is as follows: Nb is 57.95%, Si is 16%, Ti is 20%, Zr is 3%, C is 3%, and Sc is 0.05%. During the smelting process, an excess of the refining agent CoAl2O4 is added, with a mass of 0.2% of the required ingot mass. At the same time, ultrasonic treatment of 0~320 s is coupled to obtain the niobium-silicon-based superalloy.

[0022] Specific Implementation Method Two: This implementation method includes the following steps: Step 1: Raw material preparation: Based on the required ingot mass, weigh the raw materials according to the atomic ratio: Nb 57.95%, Si 16%, Ti 20%, Zr 3%, C 3%, Sc 0.05%; add CoAl2O4 in excess, with a mass of 0.2% of the required ingot mass. Step 2: Preparations for smelting: The raw materials were placed in a water-cooled copper crucible of a vacuum non-consumable arc furnace; pure Ti blocks were placed in another crucible of the vacuum non-consumable arc furnace. Step 3, Smelting: Close the furnace door and evacuate to a vacuum level of 1×10⁻⁶. -3 Below Pa, high-purity argon gas is then introduced into the furnace to 0.5 MPa. The vacuuming and argon filling process is repeated 1-2 times. During the melting process, pure Ti blocks are melted first to absorb residual oxygen, and then the raw materials are melted. After the melting is completed, button ingot samples are obtained. The button ingot samples are repeatedly melted 4-5 times, and the samples are taken out after cooling. Step 4: Refine the coupled ultrasound processing: The weighed CoAl2O4 blue powder was evenly placed on the crucible base, and then the cooled button ingot sample was placed on it. The vacuuming and argon filling steps in step three were repeated to melt the button ingot again. At the same time as the melting current was reduced, the ultrasonic treatment equipment was turned on. The ultrasonic treatment time was 0~320 s. After cooling, the niobium silicon-based high-temperature alloy button ingot with added cobalt aluminate coupled ultrasonic treatment was obtained.

[0023] This invention adds a refining agent to niobium-silicon-based superalloys to improve their room-temperature fracture toughness by controlling the size or content of silicides. Specifically, by adding the refining agent CoAl2O4 and using auxiliary ultrasonic treatment, this invention increases the number of heterogeneous nucleation sites, significantly reduces the size of the silicide phase in the niobium-silicon alloy, absorbs more cracks during fracture, and increases room-temperature fracture toughness.

[0024] Specific Implementation Method 3: In step one of this implementation method, Nb is φ 2×2 mm particles, Si is irregular thin flakes, Ti is high-purity sponge titanium, Zr is 1~2 mm irregular particles, C is carbon powder with a particle size of 5 μm, Sc is filamentous material with a particle size of φ0.5 mm of varying lengths, and CoAl2O4 is blue powder with a particle size of 150 nm.

[0025] This setup ensures more accurate weighing of low-content elements during raw material weighing, while preventing the main alloying elements in the ingot from being blown out of the crucible during smelting. Other components and connections are the same as in specific implementation methods one or two.

[0026] Specific Implementation Method Four: In this implementation method, the purity of the metal raw materials in step one is all above 99.95%. This setting ensures that as few impurities as possible are introduced during the smelting process, thus minimizing the deterioration of the room temperature fracture toughness of the niobium-silicon based alloy. Other compositions and connections are the same as in Specific Implementation Methods One, Two, or Three.

[0027] Specific Implementation Method 5: In step one of this implementation method, C and Sc are wrapped with aluminum foil. This arrangement prevents the C powder and Sc wire from being blown out of the crucible during arc initiation. Other components and connections are the same as in any of Specific Implementation Methods 1 to 4.

[0028] Specific Implementation Method Six: In step two of this implementation method, the placement order is as follows: Step 21: Place the aluminum foil containing the C powder and Sc wire at the bottom of the crucible to prevent the electric arc from blowing the C powder and Sc wire away during melting; Step 22: Place the Si wafer and Zr particles; Steps 2 and 3: Place the Ti block and Nb block on top.

[0029] This configuration ensures that the high-melting-point lumpy raw material melts first, and then encapsulates the granular or flake-shaped raw material, preventing it from being blown out of the crucible during the smelting process. It also reduces the loss of other low-melting-point metals during the smelting process. Other components and connections are the same as in any of the specific embodiments one to five.

[0030] Specific implementation method seven: In step three of this implementation method, during melting, the melting current is increased by 300 A every 5 seconds to 600 A, and maintained in the molten state for 10 to 15 seconds. After melting, the current is gradually reduced by 50 A every 10 seconds until it reaches 0 A, and then the power is turned off.

[0031] This configuration ensures a stable electric arc and thorough melting of the raw materials during the current rise and fall process of the smelting process, resulting in a composition that is as uniform as possible. Other components and connections are the same as in any of the specific implementation methods one through six.

[0032] Specific Implementation Method 8: In step four of this implementation method, the rate of increase of the melting current is consistent with that in step three. After maintaining the melt in the molten state for 20 to 30 seconds, the ultrasonic treatment device is turned on to treat the melt for 0 to 320 seconds, while the melting current is reduced to 0 A. The rate of decrease of the melting current is consistent with that in step three.

[0033] To more clearly illustrate the difference between adding and not adding the refining agent CoAl2O4, a comparison is made here with step four in specific implementation method one: Assumption: Without adding the refining agent CoAl2O4, place the cooled button ingot in a water-cooled copper crucible, repeat the vacuuming and argon filling steps in step three, and remelt the button ingot. After the melting is completed, gradually reduce the melting current to 0 A, and obtain the niobium-silicon-based high-temperature alloy button ingot after cooling.

[0034] At this point, due to the absence of the refining agent CoAl2O4, the initial crystal nuclei of the niobium-silicon-based superalloy first form on the supercooled crucible wall during solidification, and then continue to grow under higher cooling rates. The silicide phase of the niobium-silicon-based superalloy is elongated (e.g., ...). Figure 2 As shown in Example 1 (circled), due to the stress concentration effect at the tip, the slender Nb3Si phase is prone to crack initiation during fracture. The cracks easily propagate along the boundary between the narrow gray silicide phase and the white Nbss phase. The resistance during crack propagation is small, resulting in poor room temperature fracture toughness of the niobium-silicon based alloy.

[0035] In step four of this invention, CoAl2O4 blue powder is evenly placed on the crucible base, and then the cooled button ingot is placed in the water-cooled copper crucible. The vacuuming and argon filling steps in step three are repeated, and the button ingot is melted again. After melting, the melting current is gradually reduced to 0 A, and after cooling, a niobium-silicon-based high-temperature alloy button ingot with added cobalt aluminate is obtained.

[0036] The addition of CoAl2O4 as a refining agent reacts with the high-temperature melt during solidification to generate metallic cobalt. As a heterogeneous nucleation site, metallic cobalt provides a nucleation substrate for the solidification of niobium-silicon-based high-temperature melt. The silicides in the niobium-silicon-based alloy gradually transform from elongated shapes to uniform polygons with a significant reduction in size, effectively refining the microstructure. During fracture, more silicides generate cracks to absorb more energy, significantly improving the room-temperature fracture toughness of the niobium-silicon-based high-temperature alloy.

[0037] In step four of this invention, CoAl2O4 blue powder is evenly placed on the crucible base, and then the cooled button ingot is placed on it. The vacuuming and argon filling steps in step three are repeated, and the button ingot is melted again. At the same time as the melting current is reduced, the ultrasonic treatment equipment is turned on. The ultrasonic treatment time is 160 s. After cooling, a niobium-silicon-based high-temperature alloy button ingot with added cobalt aluminate coupled ultrasonic treatment is obtained.

[0038] The addition of CoAl2O4 as a refining agent reacts with the high-temperature melt during solidification to generate metallic cobalt. As a heterogeneous nucleation site, metallic cobalt provides a nucleation substrate for the solidification of niobium-silicon-based high-temperature melt. Simultaneously, under the action of coupled ultrasonic treatment, the silicides of the niobium-silicon-based alloy gradually change from uniform polygons to near-spherical shapes with a significant reduction in size, effectively refining the microstructure. During the fracture process, the silicides generate more cracks and absorb more energy, further improving the room temperature fracture toughness of the niobium-silicon-based high-temperature alloy.

[0039] In step four of this invention, CoAl2O4 blue powder is evenly placed on the crucible base, and then the cooled button ingot is placed on it. The vacuuming and argon filling steps in step three are repeated, and the button ingot is melted again. At the same time as the melting current is reduced, the ultrasonic treatment equipment is turned on. The ultrasonic treatment time is 320 s. After cooling, a niobium-silicon-based high-temperature alloy button ingot with added cobalt aluminate coupled ultrasonic treatment is obtained.

[0040] The addition of the refining agent CoAl2O4 reacts with the high-temperature melt during solidification to generate metallic cobalt. As a heterogeneous nucleation point, metallic cobalt provides a nucleation substrate for the solidification of niobium-silicon-based high-temperature melt. At the same time, under the action of coupled ultrasonic treatment for a longer period of time, the niobium-silicon-based alloy silicide is still nearly spherical and the size is slightly reduced, but its room temperature fracture toughness is reduced.

[0041] In summary, the addition of CoAl2O4 as a refining agent and the auxiliary ultrasonic treatment can provide heterogeneous nucleation points, break dendrites, and promote melt flow. The size of silicides in niobium-silicon-based superalloys gradually decreases, causing the silicides to gradually change from slender shapes to uniform polygons and near-spherical shapes. This reduces stress concentration at the fracture tip and prevents crack propagation along the boundary of silicide phases with lower room temperature fracture toughness during fracture, thereby improving the room temperature fracture toughness of niobium-silicon-based superalloys.

[0042] Specific Implementation Method Nine: In step four of this implementation method, the ultrasonic treatment equipment is non-contact. The upper part of the ultrasonic probe is in close contact with the bottom of the cold crucible, and the lower part of the ultrasonic probe is connected to the ultrasonic controller via an ultrasonic generator rod. This configuration allows the ultrasonic probe to indirectly contact the niobium-silicon-based high-temperature alloy melt, avoiding contamination of the ultrasonic probe while simultaneously performing ultrasonic treatment on the alloy melt. Other components and connections are the same as in any of Specific Implementation Methods One through Eight.

[0043] The alloy prepared by the method of the present invention is: Nb-16Si-20Ti-3Zr-3C-0.05Sc high-temperature alloy.

[0044] Combination Figures 1 to 3 Description of embodiments of the present invention: Example

[0045] Step 1: Based on the required ingot mass, weigh the raw materials according to the atomic ratio of Nb 57.95%, Si 16%, Ti 20%, Zr 3%, C 3%, and Sc 0.05%, wherein the C powder and Sc wire are wrapped in aluminum foil.

[0046] Step 2: Place the raw materials in a water-cooled copper crucible of a vacuum non-consumable arc furnace. The order of placement is as follows: first, place the aluminum foil wrapped with carbon powder and scandium wire at the bottom of the crucible to prevent the arc from blowing away the C powder and Sc wire during melting; then place the Si wafers and Zr particles, and finally place the Ti blocks and Nb blocks on top; place the pure Ti blocks in another crucible of the vacuum non-consumable arc furnace.

[0047] Step 3: Close the furnace door and evacuate to 1×10⁻⁶. -3 Below Pa, high-purity argon gas is then introduced into the furnace to 0.5 MPa. The vacuuming and argon filling process is repeated 1-2 times. During melting, pure Ti blocks are melted first to absorb residual oxygen, and then the raw materials are melted. During melting, the melting current is increased by 300 A every 5 seconds to 600 A. The current is maintained in the molten state for 10-15 seconds. After melting, the current is gradually reduced by 50 A every 10 seconds until it reaches 0 A. The power is then turned off. After melting, a button ingot sample is obtained. The button ingot is repeatedly melted 4-5 times, and the sample is taken out after cooling.

[0048] Step 4: Without adding the refining agent CoAl2O4, place the cooled button ingot in a water-cooled copper crucible, repeat the vacuuming and argon filling steps in Step 3, and remelt the button ingot. During melting, increase the melting current by 300 A every 5 seconds to 600 A, maintain it in the molten state for 20 to 30 seconds, then decrease it by 50 A every 10 seconds until it reaches 0 A. Turn off the power, and after cooling, obtain the niobium-silicon-based high-temperature alloy button ingot.

[0049] Step 5: The room temperature fracture toughness of the niobium-silicon-based superalloy without the addition of cobalt aluminate refiner and without ultrasonic-assisted treatment is 11.83 MPa·m. 1 / 2 The silicides are elongated in shape. Example

[0050] Step 1: Based on the required ingot mass, weigh the raw materials according to the atomic ratio of Nb 57.95%, Si 16%, Ti 20%, Zr 3%, C 3%, and Sc 0.05%, where C powder and Sc wire are wrapped in aluminum foil; CoAl2O4 is added in excess, with its mass being 0.2% of the required ingot mass.

[0051] Step 2: Place the raw materials in a water-cooled copper crucible of a vacuum non-consumable arc furnace. The order of placement is as follows: first, place the aluminum foil wrapped with carbon powder and scandium wire at the bottom of the crucible to prevent the arc from blowing away the C powder and Sc wire during melting; then place the Si wafers and Zr particles, and finally place the Ti blocks and Nb blocks on top; place the pure Ti blocks in another crucible of the vacuum non-consumable arc furnace.

[0052] Step 3: Close the furnace door and evacuate to 1×10⁻⁶. -3 Below Pa, high-purity argon gas is then introduced into the furnace to 0.5 MPa. The vacuuming and argon filling process is repeated 1-2 times. During melting, pure Ti blocks are melted first to absorb residual oxygen, and then the raw materials are melted. During melting, the melting current is increased by 300 A every 5 seconds to 600 A. The current is maintained in the molten state for 10-15 seconds. After melting, the current is gradually reduced by 50 A every 10 seconds until it reaches 0 A. The power is then turned off. After melting, a button ingot sample is obtained. The button ingot is repeatedly melted 4-5 times, and the sample is taken out after cooling.

[0053] Step 4: Place the CoAl2O4 blue powder evenly on the crucible base, then place the cooled button ingot in the water-cooled copper crucible. Repeat the vacuuming and argon filling steps in Step 3 to remelt the button ingot. During melting, increase the melting current by 300 A every 5 seconds to 600 A. After maintaining the current in the molten state for 20 to 30 seconds, decrease it by 50 A every 10 seconds until it reaches 0 A. After cooling, the niobium-silicon-based high-temperature alloy button ingot is obtained.

[0054] Step 5: The room temperature fracture toughness of the niobium-silicon-based superalloy with added cobalt aluminate refiner and without ultrasonic treatment is 15.59 MPa·m. 1 / 2 The room temperature fracture toughness increases; the silicide size decreases and becomes a uniform polygon. Example

[0055] Step 1: Based on the required ingot mass, weigh the raw materials according to the atomic ratio of Nb 57.95%, Si 16%, Ti 20%, Zr 3%, C 3%, and Sc 0.05%, where C powder and Sc wire are wrapped in aluminum foil; CoAl2O4 is added in excess, with its mass being 0.2% of the required ingot mass.

[0056] Step 2: Place the raw materials in a water-cooled copper crucible of a vacuum non-consumable arc furnace. The order of placement is as follows: first, place the aluminum foil wrapped with carbon powder and scandium wire at the bottom of the crucible to prevent the arc from blowing away the C powder and Sc wire during melting; then place the Si wafers and Zr particles, and finally place the Ti blocks and Nb blocks on top; place the pure Ti blocks in another crucible of the vacuum non-consumable arc furnace.

[0057] Step 3: Close the furnace door and evacuate to 1×10⁻⁶. -3 Below Pa, high-purity argon gas is then introduced into the furnace to 0.5 MPa. The vacuuming and argon filling process is repeated 1-2 times. During melting, pure Ti blocks are melted first to absorb residual oxygen, and then the raw materials are melted. During melting, the melting current is increased by 300 A every 5 seconds to 600 A. The current is maintained in the molten state for 10-15 seconds. After melting, the current is gradually reduced by 50 A every 10 seconds until it reaches 0 A. The power is then turned off. After melting, a button ingot sample is obtained. The button ingot is repeatedly melted 4-5 times, and the sample is taken out after cooling.

[0058] Step 4: Place the CoAl2O4 blue powder evenly on the crucible base, then place the cooled button ingot in the water-cooled copper crucible. Repeat the vacuuming and argon filling steps in Step 3 to remelt the button ingot. During melting, increase the melting current by 300 A every 5 seconds to 600 A. After maintaining the molten state for 20-30 seconds, turn on the ultrasonic treatment equipment to treat the melt for 160 seconds. At the same time, decrease the current by 50 A every 10 seconds until it reaches 0 A. After cooling, the niobium-silicon-based high-temperature alloy button ingot is obtained.

[0059] Step 5: The room temperature fracture toughness of the niobium-silicon-based superalloy treated with ultrasonic assistance by adding cobalt aluminate refiner is 18.72 MPa·m. 1 / 2 The room temperature fracture toughness increases; the size of the silicide further decreases and becomes nearly spherical. Example

[0060] Step 1: Based on the required ingot mass, weigh the raw materials according to the atomic ratio of Nb 57.95%, Si 16%, Ti 20%, Zr 3%, C 3%, and Sc 0.05%, where C powder and Sc wire are wrapped in aluminum foil; CoAl2O4 is added in excess, with its mass being 0.2% of the required ingot mass.

[0061] Step 2: Place the raw materials in a water-cooled copper crucible of a vacuum non-consumable arc furnace. The order of placement is as follows: first, place the aluminum foil wrapped with carbon powder and scandium wire at the bottom of the crucible to prevent the arc from blowing away the C powder and Sc wire during melting; then place the Si wafers and Zr particles, and finally place the Ti blocks and Nb blocks on top; place the pure Ti blocks in another crucible of the vacuum non-consumable arc furnace.

[0062] Step 3: Close the furnace door and evacuate to 1×10⁻⁶. -3 Below Pa, high-purity argon gas is then introduced into the furnace to 0.5 MPa. The vacuuming and argon filling process is repeated 1-2 times. During melting, pure Ti blocks are melted first to absorb residual oxygen, and then the raw materials are melted. During melting, the melting current is increased by 300 A every 5 seconds to 600 A. The current is maintained in the molten state for 10-15 seconds. After melting, the current is gradually reduced by 50 A every 10 seconds until it reaches 0 A. The power is then turned off. After melting, a button ingot sample is obtained. The button ingot is repeatedly melted 4-5 times, and the sample is taken out after cooling.

[0063] Step 4: Place the CoAl2O4 blue powder evenly on the crucible base, then place the cooled button ingot in the water-cooled copper crucible. Repeat the vacuuming and argon filling steps in Step 3 to remelt the button ingot. During melting, increase the melting current by 300 A every 5 seconds to 600 A. After maintaining the molten state for 20 to 30 seconds, turn on the ultrasonic treatment equipment to treat the melt for 320 seconds. At the same time, decrease the current by 50 A every 10 seconds until it reaches 0 A. After cooling, the niobium-silicon-based high-temperature alloy button ingot is obtained.

[0064] Step 5: The room temperature fracture toughness of the niobium-silicon-based superalloy treated with ultrasonic assistance by adding cobalt aluminate refiner is 15.54 MPa·m. 1 / 2 Fracture toughness decreased; silicide size decreased slightly.

[0065] XRD phase analysis of the niobium-silicon-based superalloys prepared in Examples 1, 2, 3, and 4, which underwent ultrasonic treatment with added cobalt aluminate, is as follows: Figure 1 As shown, circles represent Nbss, rhombuses represent Nb3Si, and plum blossoms represent Nb5Si3. With the addition of the refining agent CoAl2O4 and the increase of ultrasonic time, the characteristic peaks of Nbss gradually intensify, indicating an increase in Nbss content. As a ductile phase, Nbss exhibits good resistance to crack propagation, and its room temperature fracture toughness is improved.

[0066] The microstructure results of the niobium-silicon-based superalloys prepared in Examples 1, 2, 3, and 4, which underwent ultrasonic treatment with added cobalt aluminate, are as follows: Figure 2As shown, with the addition of the refining agent CoAl2O4 and the increase of ultrasonic time, the silicide gradually changes from a strip shape to a polygon, and then to a near-spherical shape, and the size gradually decreases.

[0067] The room temperature fracture toughness results of the niobium-silicon-based superalloys prepared in Examples 1, 2, 3, and 4, which underwent ultrasonic treatment with added cobalt aluminate, are as follows: Figure 3 As shown, with the addition of the refining agent CoAl2O4 and the increase of ultrasonic time, the room temperature fracture toughness of the niobium-silicon-based superalloy initially increased from 11.83 MPa·m. 1 / 2 It gradually increased to 18.72 MPa·m 1 / 2 When the ultrasonic treatment time was increased to 320 s, the room temperature fracture toughness decreased to 15.54 MPa·m. 1 / 2 The room temperature fracture toughness is still higher than that of the niobium-silicon-based superalloy without cobalt aluminate and without ultrasonic treatment in Example 1. When a refining agent is added and ultrasonic treatment is coupled for 320 s, cracks initiate from the silicide phase. When the silicide size is small, the Nbss phase size is also relatively small. During crack propagation, it is easy to propagate along the shortest distance between adjacent silicide phases. Therefore, the room temperature fracture toughness is lower than that of the niobium-silicon-based superalloy ultrasonically treated for 160 s.

[0068] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A niobium-silicon-based superalloy with added cobalt aluminate coupled ultrasonic treatment, characterized in that: The atomic ratios of the raw materials for this niobium-silicon-based superalloy are as follows: Nb 57.95%, Si 16%, Ti 20%, Zr 3%, C 3%, and Sc 0.05%. During the smelting process, an excess of CoAl2O4 refining agent is added, with a mass of 0.2% of the required ingot mass. The niobium-silicon-based superalloy is obtained by simultaneously coupling ultrasonic treatment for 0~320 s.

2. A method for preparing a niobium-silicon-based superalloy with added cobalt aluminate coupled by ultrasonic treatment as described in claim 1, characterized in that: It includes the following steps: Step 1: Raw material preparation: Based on the required ingot mass, weigh the raw materials according to the atomic ratio: Nb 57.95%, Si 16%, Ti 20%, Zr 3%, C 3%, Sc 0.05%; add CoAl2O4 in excess, with a mass of 0.2% of the required ingot mass. Step 2: Preparations for smelting: The raw materials were placed in a water-cooled copper crucible of a vacuum non-consumable arc furnace; pure Ti blocks were placed in another crucible of the vacuum non-consumable arc furnace. Step 3, Smelting: Close the furnace door and evacuate to a vacuum level of 1×10⁻⁶. -3 Below Pa, high-purity argon gas is then introduced into the furnace to 0.5 MPa. The vacuuming and argon filling process is repeated 1-2 times. During the melting process, pure Ti blocks are melted first to absorb residual oxygen, and then the raw materials are melted. After the melting is completed, button ingot samples are obtained. The button ingot samples are repeatedly melted 4-5 times, and the samples are taken out after cooling. Step 4: Refine the coupled ultrasound processing: The weighed CoAl2O4 blue powder was evenly placed on the crucible base, and then the cooled button ingot sample was placed on it. The vacuuming and argon filling steps in step three were repeated to melt the button ingot again. At the same time as the melting current was reduced, the ultrasonic treatment equipment was turned on. The ultrasonic treatment time was 0~320 s. After cooling, the niobium silicon-based high-temperature alloy button ingot with added cobalt aluminate coupled ultrasonic treatment was obtained.

3. The method for preparing a niobium-silicon-based superalloy with added cobalt aluminate coupled ultrasonic treatment according to claim 2, characterized in that: In step one, Nb is φ 2×2 mm particles, Si is irregular flakes, Ti is high-purity sponge titanium, Zr is 1~2 mm irregular particles, C is carbon powder with a particle size of 5 μm, Sc is filamentous material with a particle size of φ 0.5 mm of varying lengths, and CoAl2O4 is blue powder with a particle size of 150 nm.

4. The method for preparing a niobium-silicon-based superalloy with added cobalt aluminate coupled ultrasonic treatment according to claim 3, characterized in that: The purity of the metal raw materials in step one is all above 99.95%.

5. The method for preparing a niobium-silicon-based superalloy with added cobalt aluminate coupled ultrasonic treatment according to claim 4, characterized in that: In step one, C and Sc are wrapped with aluminum foil.

6. The method for preparing a niobium-silicon-based superalloy with added cobalt aluminate coupled ultrasonic treatment according to claim 5, characterized in that: In step two, the placement order is as follows: Step 21: Place the aluminum foil containing the C powder and Sc wire at the bottom of the crucible to prevent the electric arc from blowing the C powder and Sc wire away during melting; Step 22: Place the Si wafer and Zr particles; Steps 2 and 3: Place the Ti block and Nb block on top.

7. The method for preparing a niobium-silicon-based superalloy with added cobalt aluminate coupled ultrasonic treatment according to claim 6, characterized in that: In step three, during the melting process, the melting current is increased by 300 A every 5 seconds to reach 600 A. This current is maintained in the molten state for 10 to 15 seconds. After melting, the current is gradually reduced by 50 A every 10 seconds until it reaches 0 A, at which point the power is turned off.

8. The method for preparing a niobium-silicon-based superalloy with added cobalt aluminate coupled ultrasonic treatment according to claim 7, characterized in that: In step four, the rate of increase of the melting current is the same as in step three. After maintaining the melt in the molten state for 20 to 30 seconds, the ultrasonic treatment device is turned on to treat the melt for 0 to 320 seconds, while the melting current is reduced to 0 A. The rate of decrease of the melting current is the same as in step three.

9. The method for preparing a niobium-silicon-based superalloy with added cobalt aluminate coupled ultrasonic treatment according to claim 8, characterized in that: In step four, the ultrasonic processing equipment is non-contact, with the top of the ultrasonic probe in close contact with the bottom of the cold crucible, and the bottom of the ultrasonic probe connected to the ultrasonic controller via an ultrasonic generator rod.

Citation Information

Patent Citations

  • High-toughness high-temperature NbSiTiCx alloy and preparation method thereof

    CN115233063A

  • improvements concerning columbium-based alloys

    FR1343083A